Brauner Boden Ein jüdischer Blick auf die deutsche Aufarbeitung der NS-Zeit - Gallant, Katharina (Westend Verlag, 2022)
In view of the resurgence of right-wing extremist sentiments and at a time when unverified information is increasingly taken lightly as indisputable facts, it is indispensable to once again critically question the state of coming to terms with the National Socialist era in Germany. This book is dedicated to this task and focuses on German entrepreneurship, as reappraisal in this field has been very hesitant to date. Based on a Jewish perspective on the discrepancy between declarations of intent and lived reality, it is essential that Germany sincerely commits to the much-invoked "Never Again" and follows its words with deeds - in business, politics and civil society.